Thermal inspection of surface fatigue cracks in creepresisting nickel alloys; The Soviet journal of nondestructive testing; Vol. 24, № 3 - Kasatkin M. A. (1988, 1988)
The authors present the theoretical and experimental results of detecting surface fatigue cracks in metallic specimens on the basis of temperature distribution in the crack area. The aim of the work is to investigate the relationships governing the thermal inspection of surface fatigue cracks with the short time of existence of signals emitted by the defect. The adiabatic nature of surface heat exchange was solved using the finite difference method on an ES-1045 computer. Experimental thermographic results are given for VZhL12U alloy. It is shown that fatigue cracks which cannot be detected by other methods can be detected on the basis of the temperature distribution in the specimen, determined by magnetic recording amplitude thermograms. The most reliable results were obtained for the specimens coated with a developing dye used in penetrant tests of the specimens.